If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 2y)(5x + -3y) = 0 Multiply (3x + 2y) * (5x + -3y) (3x * (5x + -3y) + 2y * (5x + -3y)) = 0 ((5x * 3x + -3y * 3x) + 2y * (5x + -3y)) = 0 Reorder the terms: ((-9xy + 15x2) + 2y * (5x + -3y)) = 0 ((-9xy + 15x2) + 2y * (5x + -3y)) = 0 (-9xy + 15x2 + (5x * 2y + -3y * 2y)) = 0 (-9xy + 15x2 + (10xy + -6y2)) = 0 Reorder the terms: (-9xy + 10xy + 15x2 + -6y2) = 0 Combine like terms: -9xy + 10xy = 1xy (1xy + 15x2 + -6y2) = 0 Solving 1xy + 15x2 + -6y2 = 0 Solving for variable 'x'. Factor a trinomial. (5x + -3y)(3x + 2y) = 0Subproblem 1
Set the factor '(5x + -3y)' equal to zero and attempt to solve: Simplifying 5x + -3y = 0 Solving 5x + -3y = 0 Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. 5x + -3y + 3y = 0 + 3y Combine like terms: -3y + 3y = 0 5x + 0 = 0 + 3y 5x = 0 + 3y Remove the zero: 5x = 3y Divide each side by '5'. x = 0.6y Simplifying x = 0.6ySubproblem 2
Set the factor '(3x + 2y)' equal to zero and attempt to solve: Simplifying 3x + 2y = 0 Solving 3x + 2y = 0 Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. 3x + 2y + -2y = 0 + -2y Combine like terms: 2y + -2y = 0 3x + 0 = 0 + -2y 3x = 0 + -2y Remove the zero: 3x = -2y Divide each side by '3'. x = -0.6666666667y Simplifying x = -0.6666666667ySolution
x = {0.6y, -0.6666666667y}
| 7+2m-4=7m-7-4m | | (a+2)=(3a+9) | | -25+2x=32-x | | .07x+84532=x | | -94+x=81-6x | | (3x-1)=(5x-2) | | 136=Y(X*4-7) | | 4y=4x+2 | | 3(5x-4)-(3x+2)=16 | | 9x=5x+56 | | 4(t-2)+6t=5(2t+2)-9 | | 2x^2+3=-6x | | 9x=5x+55 | | 15-a+5a=5 | | 3x-4x=8-3 | | -7(2x-4)+5x=5(x+6) | | (x+4)=(2x+5) | | c=10-2.5 | | (x+5)=(x-9) | | y=10-2.5 | | -6(-4u+4)-5u=3(u-4)-2 | | 15-(-47)= | | 6(x-1)=-3(2-x)+3 | | -16t^2+128t+16.25=0 | | -6(y+2)=3y-9+3(2y+5) | | -x^2+3x+8=0 | | 3+7+6=2x+5+5x | | (-b^3)(d^2)=0 | | -4(v+1)=-6v-22 | | SolveV=lwhforH | | 3u-9=17(u-3) | | (4+x)+2= |